Post Ligation Cardiac Syndrome: an Educational Presentation - Silva,Isaac Azevedo (2022)
ABSTRACT Although technically simple, surgical correction of patent ductus arteriosus can have serious complications. In this context, acute ventricular failure must be remembered, as its prompt diagnosis and proper management can change clinical outcomes.